2019
DOI: 10.3390/f10100842
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Negative Impacts of Prunus serotina, Quercus rubra and Robinia pseudoacacia on Native Forest Ecosystems

Abstract: The introduction of invasive alien plant species (IAPS) can modify plant-soil feedback, resulting in an alteration of the abiotic and biotic characteristics of ecosystems. Prunus serotina, Quercus rubra and Robinia pseudoacacia are IAPS of European temperate forests, where they can become dominant and suppress the native biodiversity. Assuming that the establishment of these invasive species may alter native forest ecosystems, this study comparatively assessed their impact on ecosystems. This study further inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…Therefore, the reference ecosystem influences the effect of P. serotina invasion on alpha diversity metrics. In contrast, R. pseudoacacia impacts were not due to decreased light availability, but rather due to nitrogen fixation and increased soil nitrogen availability (Rice et al 2004), resulting in increasing alpha diversity or no impacts, similar to other studies (Sitzia et al 2012;Hejda et al 2017;Gentili et al 2019). However, still other studies revealed decreases of species diversity by R. pseudoacacia, in comparison with Betula pendula urban forests (Kowarik et al 2019), Q. cerris and Q. pubescens thermophilous forests (Lazzaro et al 2018) or shrublands on abandoned fields in China (Kou et al 2016).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the reference ecosystem influences the effect of P. serotina invasion on alpha diversity metrics. In contrast, R. pseudoacacia impacts were not due to decreased light availability, but rather due to nitrogen fixation and increased soil nitrogen availability (Rice et al 2004), resulting in increasing alpha diversity or no impacts, similar to other studies (Sitzia et al 2012;Hejda et al 2017;Gentili et al 2019). However, still other studies revealed decreases of species diversity by R. pseudoacacia, in comparison with Betula pendula urban forests (Kowarik et al 2019), Q. cerris and Q. pubescens thermophilous forests (Lazzaro et al 2018) or shrublands on abandoned fields in China (Kou et al 2016).…”
Section: Discussionsupporting
confidence: 86%
“…This may suggest that impacts of invasive trees on understory alpha diversity are more severe where resources are more limiting-such as light in Q. rubra forests and soil nutrients in poor P. sylvestris forests. This explains the high consistency among studies revealing negative effects of Q. rubra on understory vegetation (Marozas et al 2009;Woziwoda et al 2014;Gentili et al 2019) and some results revealing no impacts (Verheyen et al 2007;Chabrerie et al 2010;Gentili et al 2019) of P. serotina. Moreover, studies reported that P. serotina decreased understory plant diversity on less fertile sites resembling poor P. sylvestris forests from this study (Godefroid et al 2005; Halarewicz and _ Zołnierz 2014).…”
Section: Discussionmentioning
confidence: 85%
“…Thanks to species-specific modification of ecosystem properties (Peterken 2001;Mueller et al 2012;Castro-Díez et al 2019), they may severely influence dependent organisms, e.g. mycorrhizae (Dickie et al 2017;Rożek et al 2020), bacteria (Stanek and Stefanowicz 2019), fauna (Karolewski et al 2020;Mueller et al 2016) and plants (Taylor et al 2016;Vítková et al 2017;Gentili et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We found also that some species occur mainly in forests (Fo) on rusty soils (Rs). Q. rubra and P. serotina were intentionally introduced in forests of European countries and beyond, e.g., in Italy in temperate deciduous woodland patches of the Po plain, in the Lombardy region, or Ukraine, France, Germany, and the British Isles [ 60 , 61 ]. The soils occupied by these species are therefore mainly conditioned by places of their introduction.…”
Section: Discussionmentioning
confidence: 99%